Adsorption Studies of Copper on Rice Husk Ash (RHA) (Bangladesh Journal of Scientific and Industrial Research, 2011)
In present investigation the adsorption of copper on rice husk ash was studied by using batch technique. The quantities of copper metal before and after the treatment of their standard solutions with rice husk ash were determined by atomic absorption spectrophotometer. Percentage adsorption was calculated for RHA-Copper solution system. The effects of various parameters, such as pH of solution, contact time, temperature and adsorbate concentration were studied. It was observed that adsorption of copper increased with increasing time, temperature, pH and decreased with increasing adsorbate concentration. Adsorption process is interpreted in terms of Freundlich equation. It was found that rice husk ash can be used as a suitable adsorbent for the removal of copper from wastewater. Key words: Adsorption; Copper; Rice husk ash DOI: 10.3329/bjsir.v45i4.7382 Bangladesh J. Sci. Ind. Res. 45(4), 367-370, 2010